Comparative Analysis of Adverse Effects: Protein Kinase Inhibitors Versus Traditional Anticancer Therapies - Ioana Lavinia Radulian; Georgiana Nitulescu; Anca Zanfirescu; George Mihai Nitulescu (Scientia Pharmaceutica)
The adverse effects of protein kinase inhibitors (PKIs) and other anticancer therapies were compared using FDA Adverse Events Reporting System (FAERS) data. The dataset included 159 FDA-approved anticancer drugs (71 PKIs, 88 nonPKIs) and analyzed 8216 unique adverse event (AE) terms. PKIs showed fewer systemic toxicities, with an average of 230.1 distinct AEs per drug, compared to 537.7 in nonPKIs. Hematologic AEs were significantly lower in PKIs (e.g., febrile neutropenia: 1.93% vs. 5.25%; thrombocytopenia: 2.18% vs. 3.87%), coupled with a lower incidence of infections (6.87% vs. 14.2%) and immunosuppressive effects. However, gastrointestinal and skin-related AEs were more common in PKIs (e.g., diarrhea: 13.95% vs. 8.36%). A higher proportion AEs in the PKI group (14.57%) were classified under “Investigations”, compared to the nonPKI group (9.87%). The frequency of “Skin and subcutaneous tissue disorders” AEs was twice as high in the PKI group. Clustering analysis grouped drugs by AE profiles, showing that PKIs formed more homogeneous clusters, while nonPKIs had broader variability. Multi-kinase inhibitors with VEGFR activity were linked to dermatologic AEs, likely due to EGFR inhibition in basal keratinocytes. Despite PKIs’ targeted mechanisms, resistance remains a challenge, requiring biomarker-driven strategies. This study highlights PKIs’ improved tolerability but emphasizes using personalized treatment approaches to optimize efficacy and safety.